2014
DOI: 10.1038/srep06619
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the scale problem on the wind flow of a windbreak

Abstract: The airflow field around wind fences with different porosities, which are important in determining the efficiency of fences as a windbreak, is typically studied via scaled wind tunnel experiments and numerical simulations. However, the scale problem in wind tunnels or numerical models is rarely researched. In this study, we perform a numerical comparison between a scaled wind-fence experimental model and an actual-sized fence via computational fluid dynamics simulations. The results show that although the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Martin and Kok [77] noted that results reported in past wind tunnel studies observing grain speeds [95] and saltation heights [96,97] were likely impacted by using erodible sand beds of insufficient length in the wind tunnels [98,99]. Liu et al [100] used CFD to confirm that several flow characteristics near obstacles (e.g., windbreak fences) cannot be captured in a reduced-scale wind tunnel or numerical models and thus, results should not be extrapolated directly to natural landscapes. Sherman and Farrell [59] and Farrell [101] formalized an approach to partly test these scaling differences by evaluating two fundamental interactions between wind and sand: the apparent enhancement of the boundary roughness length associated with the presence of a saltation layer and the vertical distribution of mass flux.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and Kok [77] noted that results reported in past wind tunnel studies observing grain speeds [95] and saltation heights [96,97] were likely impacted by using erodible sand beds of insufficient length in the wind tunnels [98,99]. Liu et al [100] used CFD to confirm that several flow characteristics near obstacles (e.g., windbreak fences) cannot be captured in a reduced-scale wind tunnel or numerical models and thus, results should not be extrapolated directly to natural landscapes. Sherman and Farrell [59] and Farrell [101] formalized an approach to partly test these scaling differences by evaluating two fundamental interactions between wind and sand: the apparent enhancement of the boundary roughness length associated with the presence of a saltation layer and the vertical distribution of mass flux.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [13] investigated velocity particles near the surface in a wind tunnel and showed that the probability density function of sand particles' lift-off, incident velocities, and their vertical components were a function of sand particles and wind velocity. Liu et al [14] performed a numerical research comparison by computational fluid dynamic (CFD) with an actual-sized experimental model fence, and they realized some flow characteristics near the fence cannot be captured in the reduced-scale experimental or numerical model. Lima et al [15] found that the optimal fence height was around 50 cm, and using a fence with a height more than 1.25 m did not have reasonable economic benefits.…”
Section: Creep Saltation Suspensionmentioning
confidence: 99%
“…While most of the previous investigations (Baltaxe, 1967;Wilson, 1987;Lee and Kim, 1999;Lee et al, 2002;Wu et al, 2013;Dong et al, 2006;Telenta et al, 2014;Zhang et al, 2015;Tsukahara et al, 2012;Savage, 1963;Nordstrom et al, 2012;Telenta et al, 2014;Hatanaka and Hotta, 1997;Alhajraf, 2004;Wilson, 2004;Bouvet et al, 2006;Santiago et al, 2007;Liu et al, 2014;Bitog et al, 2009) focused on the flow characteristics over a single fence, it has been shown by means of wind-tunnel experiments (Guan et al, 2009), as well as…”
Section: Introductionmentioning
confidence: 99%